Implementasi Strategi Guru Akidah Akhlak Untuk Membentuk Karakter Siswa Berbasis Nilai-Nilai Islam Rahmatan Lil Alamiin (Isra): Di MTs Darussalam Kademangan Kabupaten Blitar - Putri, Ike Rahayu; Muzzaki, Hawwin (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
The problem of moral degradation among students provides a blurry portrait of the world of education. This study aims to reveal the implementation of Akidah Akhlak teachers in terms of Thomas Lickona's theory of morality in order to form student character based on Islam Rahmatan lil Alamin (ISRA) values at MTs Darussalam Kademangan. This research used is a qualitative approach with a case study type. In collecting data, researchers used observation, in-depth interviews and documentation methods. The results showed that the implementation of Akidah Akhlak teachers to shape student character based on ISRA values is divided into two, namely (1) in the classroom, the teacher runs the teaching module to the maximum, provides moral understanding, develops students' emotions, and provides a forum for real action about ISRA values. (2) outside the classroom, teachers act as role models and are sensitive to students when they need reprimands, advice or motivation.